Determinants of seigniorage in Pakistan - Batool, Sarah(080608); 2012 (Islamabad Department of Business Administration (Air University Main Campus), 2012)
This study is about the determinants of seigniorage in Pakistan. Its main objective is to find the factors affecting seigniorage in Pakistan using rolling regression. Rolling regression analysis was used to find on thirty five years data to determine the relationship between Central banks$1 (Bseigniorage and share of agriculture, relative volume of trade, GDP per capita and $US exchange rate. No strong case of autocorrelation was observed in the data when Durbin-Watson test was applied. s
BBA